RUMUS DAN FUNGSI MICROSOFT EXCEL - Junita Winni Palondongan; Neshia Ananta; Mahanaim Mandey; Cristania Kalisang; Femi Pasulle; Windi Midar Siana; Arimbi Tonapa; Dinda Manorek; Vianda Mangilaleng; Atrila Q. Mokoginta; Monalisa Pieter (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
In the current era of digitalization, Microsoft Excel has become one of the most popular and essential software in various fields, from business, finance, to science. The ability to process data effectively and be efficient is the key to success in various jobs. Excel formulas and functions are very important features in processing this data. By understanding and mastering Excel formulas and functions, someone can perform calculations, data analysis and data visualization more accurately and quickly.